Analisis Kebijakan Pendidikan Islam Lingkungan Jejaring Dalam Sistem Kebijakan Pendidikan Islam - Atik Likai Tanjua; Afindi; Leppe Firmansyah; Okta Viani; Asmara Yumarni (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2026)
Islamic education plays a strategic role in shaping the character, morals, and intellect of the Muslim community. Along with technological developments and globalization, the Islamic education network environment has become a crucial element in the formulation and implementation of education policy. This study aims to analyze the characteristics of the network environment, the structure and dynamics of Islamic education policy, and the interaction between the two within the digital and social contexts in Indonesia. The method used was a literature review of books, journal articles, policy documents, and publications from Islamic organizations. The results indicate that the Islamic education network is both vertical and horizontal, based on brotherhood (ukhuwah), silaturahmi (silaturahmi), and ta'awun (community-based cooperation), and supported by digital transformation through LMS (Learning Management System), online academic forums, and social media. The network strengthens advocacy, collaboration, and participatory education policy innovation, but faces challenges related to gaps in technology access and human resource capacity. Strategies for strengthening the network include digitalization, cross-institutional collaboration, human resource development, and the integration of Islamic values. With effective management, the Islamic education network not only improves the quality and equity of education but also produces inclusive, adaptive, and sustainable policies, in accordance with the principles of maqasid sharia.